INTERNATIONAL OPERATIONS MANAGEMENT IN INDIA - Rico Nur Ilham; Intan Eliana Putri; Fitri Randini; Naila Salsabila Kusayuningrum (RADJA PUBLIKA, 2023)
International Operations Management in India is becoming an increasingly important aspect in today's global business era. India, as one of the largest economies in the world, offers significant business opportunities for international companies. However, managing business operations in India also presents various challenges that need to be overcome. In facing this challenge, companies must adopt an effective strategy. The strategy includes local customization, deep understanding of the Indian market, development of local partnerships and the use of advanced information technology. In addition, it is also important to build good relations with the government, business partners and the local community. Through implementing the right strategy, companies can optimize their business operations in India. This includes efficiency in the supply chain, product and service quality improvement, product innovation relevant to the Indian market, and adaptation to consumer needs and local preferences. Management of international operations in India is a complex challenge but also offers great opportunities for companies. In dealing with these problems and optimizing the potential of the Indian market, companies need to adopt strategies that are adaptive, innovative and sustainable. Thus, companies can successfully manage their international business operations in India and gain a competitive advantage in this dynamic market. Management of international operations in India is a complex challenge but also offers great opportunities for companies. In dealing with these problems and optimizing the potential of the Indian market, companies need to adopt strategies that are adaptive, innovative and sustainable. Thus, companies can successfully manage their international business operations in India and gain a competitive advantage in this dynamic market. Management of international operations in India is a complex challenge but also offers great opportunities for companies. In dealing with these problems and optimizing the potential of the Indian market, companies need to adopt strategies that are adaptive, innovative and sustainable. Thus, companies can successfully manage their international business operations in India and gain a competitive advantage in this dynamic market.